The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1108/pr-08-2016-0194
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial orientation and the job demands-resources model

Abstract: Purpose The purpose of this paper is to examine the influence of entrepreneurial orientation (EO) within the framework of the job demands-resources (JD-R) model. Design/methodology/approach The sample of N=597 white-collars in the German media and IT industry is drawn via the professional network XING. Cross-sectional mediator models are used to test the hypothesis. Findings The processes proposed by the JD-R model find empirical support. Job demands primarily cause exhaustion while job resources increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 72 publications
1
24
0
Order By: Relevance
“…Furthermore, results found that job demand has negative impact on level of job satisfaction of employees i.e. hypothesis 6a, on the contrary, hypothesis 6b validates the study of (Ralph Kattenbach, 2018) that indicates the cognitive workload acts like a genuine job resource; it has a positive impact on job satisfaction.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…Furthermore, results found that job demand has negative impact on level of job satisfaction of employees i.e. hypothesis 6a, on the contrary, hypothesis 6b validates the study of (Ralph Kattenbach, 2018) that indicates the cognitive workload acts like a genuine job resource; it has a positive impact on job satisfaction.…”
Section: Discussionsupporting
confidence: 65%
“…In a similar vein, Hu et al (2013) reveal a mediation by an equity-based cognitive evaluation process not only between job resources and work engagement but also between job demands and burnout. These findings suggest that personal resources favorably mediate the motivational process between job resources and well-being as well as the health impairment process between job demands and exhaustion within an extended JD-R model (Ralph Kattenbach, 2018). (Molino, 2016) show that job demands can cause workaholism which in turn leads to more intense exhaustion.…”
Section: Job Demandmentioning
confidence: 88%
See 2 more Smart Citations
“…Some models that exist in experts' opinions are a model that does not provide onerous requirements for SMEs; for example, there must be collateral and bankable. Both of these conditions researchers believe will be suited to be met by SMEs, so severe orientation needs to be done (Kattenbach, R., & Fietze, S., 2018) to implement The expert's opinion concludes that the appropriate nancing is nancing derived from community social development fund, known as corporate social responsibility. Through the funding, it expected that SMEs could accelerate innovation (Kuratko, D. F. 2012).…”
Section: What Steps To Take?mentioning
confidence: 99%